Development of E-trade of industrial enterprises in the conditions of digital business transformation - Igor Kryvovyazyuk (Економічний форум)
This article reveals the influence of digital transformation of business on the development of e-commerce of industrial enterprises of Ukraine. The main goal of the study is to improve theoretical and methodological principles and develop practical recommendations aimed at the development of e-commerce of enterprises in the conditions of digital business transformation. Critical analysis of literature sources and approaches to solving the problem of e-commerce development shows insufficient attention of modern scientists to the researched issues. The urgency of solving this problem lies on the fact that in modern conditions, the importance of e-commerce is growing daily, and the digital transformation of business is designed to promote its development. The methodological basis is the system of methods used to obtain the final results of the research: generalization – when systematizing scientific research with the aim of clarifying the conceptual apparatus; abstract-logical – to improve the scientific and methodological approach to the study of the peculiarities of the development of ecommerce of enterprises in the conditions of digital transformation; economic analysis, graphical and tabular – when studying the peculiarities of the development of e-commerce of enterprises of Ukraine; regression analysis – to determine the impact of digitalization of business on the development of e-commerce; grouping – to determine the factors and reasons for inhibiting the development of e-commerce of enterprises. The object of the study is the development of e-commerce of enterprises in the conditions of digital transformation of business. The article presents the results of assessing the importance of the influence of ICT on e-commerce using the one-dimensional linear regression method, which demonstrate that in the case of improving the use of ICT by industrial enterprises of Ukraine by 0.1, this causes an increase in the share of the volume of sales of products remotely by 1.820. The directions of development of e-commerce of industrial enterprises of Ukraine in the conditions of digital transformation of business are revealed. The results of the research can be used for business structures that seek to ensure the development of e-commerce in the modern conditions of digital business transformation